2013
DOI: 10.1002/pds.3395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of FDA safety‐related drug label changes in 2010

Abstract: Drug label changes involve contributions from multiple evidence sources. The findings from this comprehensive review are consistent with previous findings and demonstrate (i) the continued importance of the spontaneous reporting system and complementary evidence sources and (ii) safety-related label changes take place years after postmarket approval, emphasizing the importance of continued drug safety surveillance throughout a product's lifecycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 6 publications
(6 reference statements)
7
83
0
Order By: Relevance
“…Lester et al [12] found that between 52 and 55 per cent of drug label changes were the result of spontaneous reporting; this demonstrates the significance of spontaneous reporting in PV activities. Spontaneous reporting involves the unsolicited generation of a signal by a healthcare provider or a patient relating to the suspicion of an ADR.…”
Section: Spontaneous Reportingmentioning
confidence: 99%
See 3 more Smart Citations
“…Lester et al [12] found that between 52 and 55 per cent of drug label changes were the result of spontaneous reporting; this demonstrates the significance of spontaneous reporting in PV activities. Spontaneous reporting involves the unsolicited generation of a signal by a healthcare provider or a patient relating to the suspicion of an ADR.…”
Section: Spontaneous Reportingmentioning
confidence: 99%
“…Spontaneous reporting during the post-marketing phase generates the majority of drug safety data, even more so than the clinical trials during the drug development process [12]. Lester et al [12] found that between 52 and 55 per cent of drug label changes were the result of spontaneous reporting; this demonstrates the significance of spontaneous reporting in PV activities.…”
Section: Spontaneous Reportingmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Lester et al evaluated safety-related drug label changes in 2010. 11 In this study, spontaneous reports were associated with 52% and 55% of label changes and anti-infectives and cardiovascular drugs were among the drug classes most frequently affected. The label change initiator was most commonly associated with adverse reactions, precautions, and warnings.…”
Section: Introductionmentioning
confidence: 99%